(untitled) (Medical Forum Monthly, 2024)
Objective: To determine and analysis of Syphilis and Associated Risk Factors in Pregnant Women Belongs to Remote Areas of Sukkur. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted on women belongs to peripheral areas of sukkur over a period of fifteen months, which beginning in May, 2012. Materials and Methods: Patient’s 5ml whole blood was collected through venepuncture technique. Data were collected by all women answered a questionnaire and by investigating Blood Sample VDRL test and FTA-ABS test. The study was conducted in a confidential manner and numbers were used to identify the participant. Results: Total 200 Pregnant women were included in the present study. Mean age of women was 25.4 years while range was 18 to 39 years. Out of the 200 samples, 6 (3.0%) were positive for active syphilis. Majority was belonging to low socioeconomic group of population. Conclusion: Active syphilis infection in pregnant women belongs to remote areas with low socioeconomic level were significantly disquieting. Alarming results of this study suggestive that seropositive status is often discovered in routine serological studies during pregnancy at health centers and efficient prolonged treatment of mother were available.